DEKONSTRUKSI HOKUM PERTANAHAN DI BIDANG PERKEBUNAN DI INDONESIA (AlternatifPembaharuan Hukum Pertanahan di Bidang Perkebunan) - Firman Muntaqo (Jurnal Hukum, 2005)
Regulation and land law policy on plantation not to realize the aim of UUPA yet. Even,  the plantation farmer be marginalized to labors on the Plantation Corporation,  and be the landless.  Economically,  the plantation farmer is very depending on the Plantation Corporation (state,  national private corporation, joint venture although foreign corporation) that have facilitated by the government to have widespread land. Both conditions above caused of The New Order   Regime   implemented   capitalistic   politic   with   classical   capitalist paradigm and state authoritarian to reach high economic growth.  It's  caused be injustice for the people.  Deconstruction on the plantation  land law is a way to bring justice for  the people,  especially for the plantation farmer  by giving access be owner to plantation land.